Kafka’s Students and the Inoperation of Knowledge: An Investigation into the Power of Stupidity - Listik, Yonathan (Labyrinth, 2025)
This article will explore how configurations of the student in Kafka's literature represent a specific relation to knowledge. The central argument will be that their attitude represents a form of rendering knowledge inoperative, therefore representing a disruption of power structures. The emblematic figure of this posture will be the worst student in Kafka's Abraham. This disruptive posture will be denoted as a form of stupidity. The interest in stupidity comes from its abundant presence as a motif in contemporary social and political issues. Stupidity is a form of otherness and belongs always to the other: the accusation of stupidity is always directed at the alternative position. The text will use the student in Abraham to challenge the common-sense framing of stupidity as constituting an unwarranted invasion, deemed inconsistent with the age of enlightenment and political progress, and that must therefore be eradicated.